Preserving Tradition Amid Disruption: A Systematic Literature Review (SLR) of Pesantren Development in Indonesia - Akhmad, Satria Kamal (The Institute of Research and Service Community IPMAFA Pati, 2024)
This systematic literature review aims to present recent findings on the development of pesantren in Indonesia and to examine the efforts made by pesantren to address the challenges of a global society while preserving the traditional values inherent to pesantren during the era of disruption. This study employs the Systematic Review of Literature (SLR) methodology, structured according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The data collected for this research consists of peer-reviewed articles published between 2020 and 2024. A total of 24 articles that met the inclusion criteria were analyzed and serve as references for this study. The analysis reveals that pesantren remain relevant to the demands of the times and the needs of society. The implementation of modern curricula, the integration of technology, and the involvement of local communities are key strategies employed by pesantren to maintain a balance between innovation and tradition. This research highlights the significant role of pesantren leaders as central figures in guiding the modernization of pesantren without compromising traditional values. The findings of this systematic literature review are expected to provide strategic insights for pesantren to remain relevant and adaptive to the dynamic developments in the global societal ecosystem.